2008
DOI: 10.1021/bi8007033
|View full text |Cite
|
Sign up to set email alerts
|

Role of the N- and C-Lobes of Calmodulin in the Activation of Ca2+/Calmodulin-Dependent Protein Kinase II

Abstract: Understanding the principles of calmodulin (CaM) activation of target enzymes will help delineate how this seemingly simple molecule can play such a complex role in transducing Ca2+-signals to a variety of downstream pathways. In the work reported here, we use biochemical and biophysical tools and a panel of CaM constructs to examine the lobe specific interactions between CaM and CaMKII necessary for the activation and autophosphorylation of the enzyme. Interestingly, the N-terminal lobe of CaM by itself was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 41 publications
3
39
1
Order By: Relevance
“…The determined binding affinities were in agreement with affinities determined for the full-length enzyme [33]. Ca 2+ /CaM bound to CaMKI and CaMKIV with >20-times higher affinity.…”
Section: Resultssupporting
confidence: 81%
“…The determined binding affinities were in agreement with affinities determined for the full-length enzyme [33]. Ca 2+ /CaM bound to CaMKI and CaMKIV with >20-times higher affinity.…”
Section: Resultssupporting
confidence: 81%
“…Fl-A 1588 had a much weaker affinity for each individual EF-hand domain of CaM ( K d of 2.41 ± 0.32 μM for CaM 1–80 and K d of 14.4 ± 6.4 μM for CaM 76–148 ) as compared to full-length CaM 1–148 . Although the N-domain of CaM has been reported to be sufficient to promote initial attachment and activation of CaMKII [45], in most cases where there is a difference between the domains of CaM, it is the interaction of a target with the C-domain of CaM that is more energetically favorable. Thus, the observation that the N-domain of CaM binds to Fl-A 1588 with a 6-fold more favorable equilibrium constant than that of the CaM C-domain is unusual compared to the majority of CaM target interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Simulations showed that the fast binding N lobe of calmodulin is much more sensitive to calcium channel location than the slow binding C lobe, and that saturated calmodulin N lobe itself forms a distinct gradient within the spine. Because calcium binding to N or C lobes of calmodulin differentially activates CaMKII (Forest et al, 2008), this may be a mechanism by which calcium location can affect plasticity.…”
Section: Locationmentioning
confidence: 99%